Biogeochemical attenuation of nitrate in a sandy subterranean estuary: Insights from two stable isotope approaches. (26th August 2020) - Wong, Wei Wen; Applegate, Andrew; Poh, Seng Chee; Cook, Perran L. M.
Abstract: The role of permeable sediments and subterranean estuaries as coastal nutrient filters is a question of key interest, particularly in areas with high nitrogen loadings. Here, we evaluated the effectiveness of a sandy subterranean estuary in cycling and removing nitrate using stable isotopes of N and O at natural (δ 15 N‐NO3 − and δ 18 O‐NO3 − ) and enriched levels ( 15 N). Isotopes were used in conjunction with flow through reactors under anoxic conditions to quantify (1) the overall enrichment factor ( 15 ε) of nitrate removal processes which was then applied to estimate the in situ percentage of nitrate removal within the subterranean estuary and (2) the potential rates of denitrification, dissimilatory nitrate reduction to ammonium, and anammox. We found that 15 ε varied between −24 and −34‰ and were positively correlated with nitrate concentrations and the percentage of organic carbon added to the sediments. Using these 15 ε values in a Rayleigh distillation model resulted in an estimated average of 34% ± 14% nitrate removal within the subterranean estuary, less than half of the percentage estimated using the nitrate‐salinity mixing model (66% ± 28%). Denitrification was the most dominant nitrate removal pathway within the subterranean estuary with potential rates among the highest denitrification rates reported for both permeable and cohesive sediments. The contribution of dissimilatory nitrate reduction to ammonium showed significant seasonal variation while the rates of anammox were consistent throughout the study. We suggest that the spatial shift of the subterranean estuary is the most likely explanation for the seasonal differences in the rates of denitrification and dissimilatory nitrate reduction to ammonium.